The Impact of Artificial Intelligence Utilization on Advocacy Practices and Professional Ethics in the Legal Field - Darmawan, Andri; Soesatyo , Bambang (Devotion : Journal of Research and Community Service, 2025)
The integration of Artificial Intelligence (AI) in legal practice has brought both transformative advancements and significant ethical challenges. This study examines the role of AI in enhancing advocacy practices, including legal research, document automation, and case prediction. Despite its potential for improving efficiency and accessibility, AI raises concerns regarding professional ethics, particularly around issues such as client confidentiality, accountability, and the independence of advocates. Using a normative approach and literature review, this research aims to analyze the implications of AI in the legal field, focusing on its impact on the advocacy profession and the ethical dilemmas it creates. The findings reveal that while AI can streamline administrative tasks and support data-driven decision-making, it also presents risks such as data security breaches and loss of human judgment in complex legal cases. The study highlights the necessity for stronger ethical guidelines and regulatory frameworks to safeguard client interests and preserve the integrity of the legal profession. This research emphasizes the importance of integrating AI into legal practice while maintaining a balance between technological advancement and ethical responsibility.